Den eneste sande bog - Gundersen, Karin (Passage - Tidsskrift for litteratur og kritik, 2015)
Karin Gundersen: “The Only True Book” A famous reflection in Proust’s In Search of Lost Time reads as follows: “[…] I slowly became aware that the essential book, the only true book, was not something the writer needs to invent, in the usual sense of the word, so much as to translate, because it already exists within each of us. The writer’s task and duty are those of a translator” (Finding Time Again, translated by Ian Patterson, London, Penguin Books, 2003, p. 199). This enigmatic statement, which says that the only true book cannot be read before it has been translated by the writer who carries it within him, implies that the book we read is not the original. Reinserted in its context, the statement seems to rely on an essential Proustian aesthetics and hence his theory of truth, style and metaphor. The present essay tries to solve, at least in part, the enigma posed by Proust.